MEDICAL INFORMATION IN THE STRUCTURE OF COGNITIVE THERAPY FOR PANIC DISORDER - A. M. Burno (Неврология, нейропсихиатрия, психосоматика)
The paper describes the procedure of cognitive therapy for panic disorder, which is based on the explanation of the nature of physical and psychopathological symptoms of anxiety.